Empowering Cadres to Improve Perception of Breast Milk Adequacy through Comprehensive Breastfeeding Education - Elly Wahyuni; Renta Handika; Rialike Burhan (CV Media Inti Teknologi, 2026)
Background of study: Stunting is a manifestation of growth failure that begins in the womb until the child is two years old. According to the World Health Organization (WHO), the prevalence of stunting increased from 144 million cases in 2020 to 149.2 million cases in 2021. In Sido Luhur village, in January 2024, there were 10 undernourished toddlers, and in May this number increased to 11, 6 of whom were still toddlers. Exclusive breastfeeding is one way to prevent stunting, as breast milk contains nutrients that are crucial for a child's growth and development. The perceived crisis of insufficient breast milk experienced by mothers during breastfeeding has become a rumor that prevents all babies from being breastfed until two years old. Comprehensive breastfeeding education is needed from pregnancy for mothers to strengthen their intentions and build confidence and efficacy in breastfeeding for two years. To develop partner villages through cadre empowerment activities to improve perceptions of breast milk sufficiency through Comprehensive Breastfeeding Education in Sidoluhur Village, Sukaraja District, Seluma Regency. Methods: This community service program was conducted using the concept of empowering cadres and pregnant women in Sidoluhur Village. The activity began with coordination with the Sukaraja Sub-district Head, the Village Head, the Health Center leadership, and the village midwife. The activity began with a joint commitment, a pre-test of knowledge before the training, the provision of materials related to Comprehensive Breastfeeding Education, cadre training, a post-test after the training, followed by a follow-up plan for mentoring pregnant women, and monitoring and evaluation of the Community Service activities. Results: There was an increase in knowledge among all cadres and pregnant women after the pre-post test. Conclusion: All cadres and pregnant women understood breastfeeding success, including knowledge, correct breastfeeding steps, infant attachment, and breast milk sufficiency in Sidoluhur Village, Sukaraja District, Seluma Regency.